2019
DOI: 10.5194/isprs-annals-iv-2-w6-47-2019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task Deep Learning With Incomplete Training Samples for The Image-Based Prediction of Variables Describing Silk Fabrics

Abstract: <p><strong>Abstract.</strong> This paper presents a method for the classification of images of silk fabrics with the aim to predict properties such as the place and time of origin and the production technique. The proposed method was developed in the context of the EU project SILKNOW (<a href="http://silknow.eu/"target="_blank">http://silknow.eu/</a>). In the context of classification, we address the problem of limited as well as not fully labelled data and investigate the connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…As explained in Section 3.3.2, we are now dealing with an expanded set of semantic properties as well as with images from various collections. Preliminary experiments show that overall accuracies of 60-88% can be achieved, which is considerably worse than the results achieved in [80]. A possible explanation for this is the expanded set of properties, which also leads to a more complex class structure for each property.…”
Section: Digital Image Recognition: From Cultural Heritage To Productmentioning
confidence: 85%
See 2 more Smart Citations
“…As explained in Section 3.3.2, we are now dealing with an expanded set of semantic properties as well as with images from various collections. Preliminary experiments show that overall accuracies of 60-88% can be achieved, which is considerably worse than the results achieved in [80]. A possible explanation for this is the expanded set of properties, which also leads to a more complex class structure for each property.…”
Section: Digital Image Recognition: From Cultural Heritage To Productmentioning
confidence: 85%
“…In this scenario, we assessed the impact of considering only complete training samples (MTL-C) as well as considering complete and incomplete samples (MTL-I). Our experiments, the details of which are presented in [80], have shown that the multi-task learning approach leads to a better classification performance compared to the single-task learning approach, but only when exclusively complete samples are used. The results of this approach are discussed in Section 4.2.1.…”
Section: Multi-task Learning With Training Samples For the Image-basementioning
confidence: 96%
See 1 more Smart Citation
“…describing the time or place of production of a fabric, is very important for art historians, but it is not provided in a standardized way, and sometimes important pieces of information are missing. In the context of an EU H2020 project (SILKNOW 2019), a multi-task CNN based on ResNet (He et al 2015) was developed that simultaneously predicts the production time, the production place and the production technique from a digital image, deriving the training data automatically by analyzing existing collections (Dorozynski, Clermont, and Rottensteiner 2019). The results show that by combining these prediction tasks, the accuracy of prediction is increased if high-quality training samples are used.…”
Section: Close Range Applicationsmentioning
confidence: 99%
“…The annotations for these properties are incomplete, so that there is a considerable number of incomplete samples. The dataset used in this paper is identical to the one used by Dorozynski et al (2019). It was generated automatically from the online collection (IMATEX, 2018); in this process, the raw annotations were mapped to a standardized class structure.…”
Section: Triplet Trainingmentioning
confidence: 99%